Evaluation of Structural Dynamic Parameters of the Old Truss Bridges Using Smartphone-Embedded Sensors - Faisal, Muhammad Hanif; Putranto, Alan; Ismah, Julia Nurzata; Rayani, Annisa Dwi (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2026)
Bridges are critical components of transportation infrastructure that experience continuous dynamic loading from traffic and environmental factors, leading to gradual deterioration of structural performance. Conventional Structural Health Monitoring (SHM) systems are often constrained by high cost and operational complexity. This study evaluates the application of smartphone-embedded accelerometers combined with the Ambient Vibration Test (AVT) method to identify the dynamic parameters of old steel truss bridges in Ketapang, West Kalimantan. A non-destructive and cost-effective approach was employed by utilizing daily traffic as a natural excitation source. Several bridges were selected based on service age, visible deterioration, and operational condition. Vibration data were collected using the Resonance Android application, which records acceleration and processes it into frequency spectra. Dominant frequencies and damping ratios were extracted and analyzed to assess the dynamic response of the structures. Field measurements on the Pawan 1 and Pawan 2 bridges revealed that several parameters—such as natural frequency, displacement, and damping ratio—exceeded standard thresholds, indicating potential structural degradation. These findings demonstrate that smartphone-based monitoring can serve as an effective preliminary diagnostic tool, providing valuable insights to support maintenance decisions and guide further detailed structural assessments.